Transforming Listening Education: Leveraging VlogNow for Effective Video-Based Learning - Risfi, Rihhadatul Aisy; Hurriyatus Sa’adiyah; Rita Febrianta; Wira Wahyuni (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2025)
The research problem in Arabic languange learning at this school includes:relience solely on lecture and Q&A methods, lack of student attantion in listening skills, and difficulty for teachers in develop media in listening. Therefore, the objektive of this research is to develop a vidio learning media using the VlogNow application at MTsN 2 Pasaman Barat School And to determine the effectiveness of using video media in learning Arabic language.. The research method employed is “Developmen Research”(Research and development) using the ADDIE model (Analysis, Design, Development,Implementation, Evaluation). Focusing only on the third stage,which is development because time constraints Based on the results, it was found that at learning material and media design, rated as “excellent” using the Likert Scale formula. In conclusion,this study suggests that the vidio media using the VlogNow application can be implemented effectively in Arabic language learning procces.